Riding for Caesar the Roman emperors' horse guards - Speidel, Michael P. 1937- (Batsford, 1994)
Epigraphik - Donauraum - Siedlung.
Keywords: Rome - Armée - Cavalerie - Empire romain; Kavallerie; Leibgarde; Kaiser; Rom; Römisches Reich